Production systems: Biophysical and economic environment and constraints - Takeshima, Hiroyuki; Bakare, Oladele Samuel (University of Pennsylvania Press, 2016)
The objective of this chapter is to provide a descriptive overview of the current rice production systems in Nigeria, their underlying biophysical and socioeconomic constraints, and their potential for expanding rice production. The chapter is organized as follows. First, we describe current production technologies and practices in use in Nigeria, such as the uses of modern inputs (improved varieties and fertilizer) and technologies (irrigation and mechanization). From this information, a typology of rice-producing households in Nigeria is determined according to the type of technologies and production environment and their capacity to expand rice production in the short to medium term. In the second and third sections, we review some of the key biophysical and socioeconomic constraints, respectively, that affect the potential for expanding rice production in different parts of the country. We show, for example, that the typical rice-production environments in Nigeria, such as climate, water access, and soils, may not be as favorable as they are in major rice-producing regions of Asia. Nevertheless, compared to other tropical West African countries, the prevalence of a lowland rice ecology in Nigeria offers it the greatest potential in the region for production growth, except for certain socioeconomic constraints that prevent households from adopting modern inputs and improved technologies. Based on this review, we conclude the chapter by summarizing the key characteristics of current rice-production environments in Nigeria.